ESTABLISHMENT, CURRENT STATE AND PROSPECTS OF POLITICAL RELATIONS BETWEEN AZERBAIJAN AND SERBIA - Гулієва, Н (Навчально-науковий інститут міжнародних відносин КНУ імені Тараса Шевченка, 2022)
The article examines the establishment, dynamics and current state of political and diplomatic relations between the Republic of Azerbaijan and the Republic of Serbia, development trends and reasons hindering the development of political relations, as well as targeted visits of heads of state and government. It also analyzes in detail the role of organizations engaged in cooperation between the two countries in the political sphere, the activities of the intergovernmental commission, the Inter-Parliamentary Group and other issues.

У статті розглянуто встановлення, динаміку та поточний стан політико-дипломатичних відносин між Азербайджанською Республікою та Республікою Сербія, тенденції розвитку та причини, що перешкоджають розвитку політичних відносин, а також цілеспрямовані візити глав держав та урядів. Тут також детально проаналізовано роль органів, що здійснюють співпрацю між двома країнами в політичній сфері, діяльність міжурядової комісії, міжпарламентської групи та інші питання.
СТВОРЕННЯ, ПОТОЧНИЙ СТАН І ПЕРСПЕКТИВИ ПОЛІТИЧНИХ ВІДНОСИН МІЖ АЗЕРБАЙДЖАНОМ І СЕРБІЄЮ